2020
DOI: 10.1029/2020wr027518
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Flow and Homogenization in Anisotropic Media

Abstract: The evolution of heterogeneous and anisotropic media in the uniform dissolution regime (low Damköhler number) is studied here using a numerical network model. The uniform dissolution extensively homogenizes the medium and therefore the flow field. The homogenization is further enhanced when the surface reaction is transport controlled-when slow diffusion of dissolved ions away from the mineral surface leads to the reduction of the global dissolution rate. Under those conditions, diffusive transport is more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 131 publications
(223 reference statements)
0
15
0
Order By: Relevance
“…The variable L included in Equation suggests the important role of system size along the flow direction in the pattern transition. The result indicates that the uniform dissolution regime is scale‐dependent: the concentration field will fully develop downstream and leads to wedge dissolution if the system length, L , is large enough, whereas otherwise the uniform dissolution is observed (Li et al., 2008; Roded et al., 2020). Theoretical analysis and numerical simulation in three‐dimensional fractures have also demonstrated that fracture length plays an important role in the transition between wormhole and uniform dissolution patterns (Li et al., 2008; Starchenko & Ladd, 2018; Wang et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variable L included in Equation suggests the important role of system size along the flow direction in the pattern transition. The result indicates that the uniform dissolution regime is scale‐dependent: the concentration field will fully develop downstream and leads to wedge dissolution if the system length, L , is large enough, whereas otherwise the uniform dissolution is observed (Li et al., 2008; Roded et al., 2020). Theoretical analysis and numerical simulation in three‐dimensional fractures have also demonstrated that fracture length plays an important role in the transition between wormhole and uniform dissolution patterns (Li et al., 2008; Starchenko & Ladd, 2018; Wang et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…To isolate the effect of mineral heterogeneity that will obscure the effect of reaction and transport on morphological evolution, some simulations with single‐mineral have been performed recently as a precursor to understanding how the coupled effect of reaction and transport at the pore scale determines the evolution of the flow channels (Li et al., 2021; Noiriel & Soulaine, 2021; Roded et al., 2020; You & Lee, 2021). These studies show that when mass transport near the surface is slower than surface reaction, dissolution in the channels is transport‐controlled and the original rough channels are smoothed and flattened (Noiriel & Soulaine, 2021; Roded et al., 2020; You & Lee, 2021). When transport near the surface is faster than surface reaction, reaction‐controlled dissolution will preserve the original channel geometry (Roded et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, following the dissolution in each timestep the geometrical properties are updated (see e.g., Bekri et al., 1995; Detwiler & Rajaram, 2007; Lichtner, 1991). Below, the PNM and main equations are succinctly described; for detailed description see in the SI and previous works (Budek & Szymczak, 2012; Roded et al., 2020).…”
Section: The Pore Network Modelmentioning
confidence: 99%
“…Much attention has been focused on the dynamics of dissolution processes in Hele‐Shaw cells (parallel plates) or in porous media (Daccord, 1987; Fu et al., 2015; Golfier et al., 2002; Jiménez‐Martínez et al., 2020; Ladd et al., 2020; Roded et al., 2020; Song et al., 2014; Szymczak & Ladd, 2011b), which provides insights into the formation of dissolution patterns. Generally, for a slow flow rate, the acid is consumed entirely before invading farther, producing compact dissolution.…”
Section: Introductionmentioning
confidence: 99%